Vascularized Bone-Mimetic Hydrogel Constructs by 3D Bioprinting to Promote Osteogenesis and Angiogenesis - Takahisa Anada (International Journal of Molecular Sciences, 2019)
Bone is a highly vascularized tissue with a unique and complex structure. Long bone consists of a peripheral cortical shell containing a network of channels for vascular penetration and an inner highly vascularized bone marrow space. Bioprinting is a powerful tool to enable rapid and precise spatial patterning of cells and biomaterials. Here we developed a two-step digital light processing technique to fabricate a bone-mimetic 3D hydrogel construct based on octacalcium phosphate (OCP), spheroids of human umbilical vein endothelial cells (HUVEC), and gelatin methacrylate (GelMA) hydrogels. The bone-mimetic 3D hydrogel construct was designed to consist of a peripheral OCP-containing GelMA ring to mimic the cortical shell, and a central GelMA ring containing HUVEC spheroids to mimic the bone marrow space. We further demonstrate that OCP, which is evenly embedded in the GelMA, stimulates the osteoblastic differentiation of mesenchymal stem cells. We refined the design of a spheroid culture device to facilitate the rapid formation of a large number of HUVEC spheroids, which were embedded into different concentrations of GelMA hydrogels. It is shown that the concentration of GelMA modulates the extent of formation of the capillary-like structures originating from the HUVEC spheroids. This cell-loaded hydrogel-based bone construct with a biomimetic dual ring structure can be potentially used for bone tissue engineering.